PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI METODE ARCS DENGAN MENGGUNAKAN MEDIA GAMBAR - Nurhikmah (Pascasarjana IAIN Sorong, 2023)
The purpose of this study is to describe the poetry writing ability of grade VIII MTs students of Sorong City. The low ability to write poetry is caused by learning to write poetry that has not been carried out properly so that grade VIII students have difficulty when asked to write poetry.Therefore, the necessary learning strategies and instructional media fun and appropriate. To overcome these problems ARCS Metode and media images of events contained in the newspaper in teaching poetry writing class VIII MTs Sorong Affairs. The research was conducted in two cycles. Each cycle consists of planning, action, observation and reflection. The results of this study indicate the existence of a process of learning, improvement, and change behavior in a positive direction.